Penerapan Teknologi Budidaya Ikan Air Tawar Dengan Metode Maxiras dan Aquaponic (Studi Kasus: Kelompok Tani Ikan Desa Kalijaran) - Cahya Vikasari; Murni Handayani; Oto Prasadi (Politeknik Negeri Cilacap, 2020)
Plant cultivation in the village of Kalijaran focuses on rice plants and fish farming with ponds. Some weaknesses of the ground pool are the condition of the soil that is prone to leakage, the ground pool is also difficult to control predatory animals, water discharge as well as water pressure, especially during heavy rain. Community service activities are carried out by applying the method of maxiras, namely carrying out the preparation of tools and materials, installation, training, mentoring and evaluation which are expected to enable more varied plants cultivation and more optimal fishery products, for example using the Ras Maxi method during agricultural activities with the aquaponic method. The purpose of this activity is to be able to create a creative community to cultivate fish and at the same time grow plants using the Maxi Race method. The result of this activity is an increase in the knowledge and skills of fish farmer groups about aquaculture with the Ras Maxi method so that the community can be more economically independent and creative.